Tool to monitor fruit and vegetable intake - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The questionnaires were developed in the local language of Nigeria and Vietnam, validated, and used in two data collection rounds. The link provided goes to the results from Nigeria.